Neurosarcoidosis in a public safety net hospital: a study of 82 cases - Dorman, James; Warrior, Lakshmi; Pandya, Vishal; Sun, Ying; Ninan, Jacob; Trick, William; Zhang, Helen; Ouyang, Bichun (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2019)
Objective: To characterize clinical presentation, laboratory and imaging data, and treatment outcomes for neurosarcoidosis in an urban safety net hospital. Methods: The research database of Cook County Health and Hospitals system was queried for all cases of sarcoidosis from 2006 to 2013. These cases plus those identified through a survey of neurology faculty were reviewed and flagged if suspected to be neurosarcoidosis. Data were extracted in a standardized fashion, upon review by two experienced neurologists; patients were classified as definite, probable or possible neurosarcoidosis. Disagreements on classification were resolved by consensus conference. Results: 1706 cases of sarcoidosis were identified, with 82 (4.8%) classified as neurosarcoidosis. The cohort was predominantly African American (89%). Six were classified as definite, 34 as probable, and 42 as possible neurosarcoidosis. Neurosarcoidosis was the presenting symptom of sarcoidosis in 74% of cases. The most common presenting phenotype was myelopathy (21.7%), followed by optic nerve/chiasm involvement (16.0%) and epilepsy (11.3%). The facial nerve was involved in only 2% of cases. Chest x-ray showed abnormalities of sarcoidosis in 43.3% of cases, while chest CT did so in 78.6%. Corticosteroids were the initial treatment in 91% of cases, and outcomes were good in 53% of cases. Conclusion: Neurosarcoidosis remains a challenging diagnosis with the majority of patients without a previous diagnosis of systemic sarcoidosis. Chest imaging was supportive of the diagnosis in a majority of patients. Our cohort differs from others in the literature due to a low prevalence of facial nerve involvement. Prospective registry studies are needed.